The Dysexecutive Syndrome Associated with Ischaemic Vascular Disease and Related Subcortical Neuropathology: A Boston Process Approach - Melissa Lamar; Cate C. Price; Tania Giovannetti; Rod Swenson; David J. Libon (Behavioural Neurology)
The introduction of diagnostic criteria for vascular dementia has helped to re-define the impact of various subcortical neuropathologies on aging; however, state-of-the-art neuroimaging techniques and autopsy studies suggest that not all structural brain alterations associated with vascular dementia are exclusive to this neurodegenerative process alone. Thus, a detailed analysis of the cognitive phenotype associated with ischaemic vascular disease is key to our understanding of subcortical neuropathology and its associated behaviors. Over the past twenty years, we have operationally defined this cognitive phenotype using the Boston Process Approach to neuropsychological assessment. This has led to both an empirical, as well as a theoretical understanding of three core constructs related to the dysexecutive syndrome associated with ischaemic vascular disease affecting periventricular and deep white matter as well as subcortical structures connecting these regions with the prefrontal cortex. Thus, difficulties with mental set, cognitive control and mental manipulation negatively impact executive functioning. This review will outline the subtle markers underlying this prefrontal dysfunction, i.e., the dysexecutive phenotype, associated with ischaemic vascular disease and relate it to fundamental impairments of gating subserved by basal ganglia-thalamic pathways within and across various dementia syndromes.